PENGARUH MODEL PEMBELAJARAN TALKING STICK TERHADAP KEMAMPUAN BERBICARA SISWA PADA MATA PELAJARAN BAHASA INDONESIA KELAS III SDN 95 PALEMBANG - Ramika, Amaeliana; Wardiah, Dessy; Notosutanto Arhon Dhony, Nugroho (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The problem in this study is the Lack of Student Confidence Most students in grade III of SDN 95 Palembang feel less confident when speaking in front of the class, which hinders their ability to speak fluently and clearly. This study aims to analyze the effect of the Talking Stick learning model on students' speaking skills in Indonesian subjects in grade III of SDN 95 Palembang. The method used in this study is a quantitative method. The data collection techniques used are tests and documentation. Based on the analysis of the results of the research that has been done, the researcher can conclude that the Talking Stick learning model has an effect on students' speaking skills. Student learning outcomes are higher when using the Talking Stick learning model. This is also shown in the results of the r count value which is smaller than the r table or r count 0.1450 <r table 0.9969. This means that the speaking ability of grade III students in Indonesian language learning at SDN 95 Palembang are included in the very good category.